2021
DOI: 10.3390/jcm10194440
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Dentinal Tubule Penetration of Endodontic Sealers in Warm Vertical Compaction by Direct Detection via SEM Analysis

Abstract: Sealer staining using rhodamine B dye to investigate the penetration depth of endodontic sealers was proven unsuitable for this purpose. This study aimed to investigate the sealer penetration depth into dentinal tubules by scanning electron microscopy (SEM). Root canals of 52 human upper central incisors were instrumented using the ProTaper Gold NiTi system (Dentsply Sirona, York, PA, USA) up to size F3. After irrigation with sodium hypochlorite and citric acid combined with ultrasonic activation, the root can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Tubule penetration enhances the contact area between dentin and root filling materials, improving the sealing of the root canal system. Nonetheless, our study revealed, consistent with previous research performed by Schmidt et al [ 50 ] (TotalFill BC sealer), Song et al [ 57 ] (EndoSeal MTA), and Atmeh et al [ 56 ] (BioRoot), that the depth of extension for bioceramic sealers is relatively modest, with no differences between tested materials. RSSE penetrated more deeply into the dentin tubules in comparison to the bioceramic sealers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tubule penetration enhances the contact area between dentin and root filling materials, improving the sealing of the root canal system. Nonetheless, our study revealed, consistent with previous research performed by Schmidt et al [ 50 ] (TotalFill BC sealer), Song et al [ 57 ] (EndoSeal MTA), and Atmeh et al [ 56 ] (BioRoot), that the depth of extension for bioceramic sealers is relatively modest, with no differences between tested materials. RSSE penetrated more deeply into the dentin tubules in comparison to the bioceramic sealers.…”
Section: Discussionsupporting
confidence: 92%
“…Scanning electron microscopy (SEM) has been deployed in previous studies to highlight the sealer characterization, to analyze the sealer–dentin interface and sealer’s penetration into dentinal tubules [ 50 , 51 , 52 , 53 , 54 , 55 ]. In similar studies, a comparable number of samples were selected for SEM investigation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The small BCS particle size (~2 μm) may enhance penetration of the sealer into the groove site dentine, which is generally sclerotic, containing fewer and smaller dentinal tubules [18]. A particle size of up to 8 μm was reported for AH Plus [19], therefore, less penetration occurred compared with the BCS group. In the non‐groove site, AH Plus sealer penetration using WHC/ERS may be improved by vertical compaction force and heat from the tip of the plugger [19].…”
Section: Discussionmentioning
confidence: 99%
“…A particle size of up to 8 μm was reported for AH Plus [19], therefore, less penetration occurred compared with the BCS group. In the non‐groove site, AH Plus sealer penetration using WHC/ERS may be improved by vertical compaction force and heat from the tip of the plugger [19]. The viscosity of AH Plus after heat application is lower for deeper dentinal tubule penetration.…”
Section: Discussionmentioning
confidence: 99%
“…No ultrasonic irrigation was undertaken to avoid artifacts caused by sealer removal from the tubules. 20 Finally, the prepared slices were dried.…”
Section: Dentinal Tubules Penetration Measurementmentioning
confidence: 99%